If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2y = 7x + -1y Solving 4x + 2y = 7x + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4x + -7x + 2y = 7x + -7x + -1y Combine like terms: 4x + -7x = -3x -3x + 2y = 7x + -7x + -1y Combine like terms: 7x + -7x = 0 -3x + 2y = 0 + -1y -3x + 2y = -1y Add '-2y' to each side of the equation. -3x + 2y + -2y = -1y + -2y Combine like terms: 2y + -2y = 0 -3x + 0 = -1y + -2y -3x = -1y + -2y Combine like terms: -1y + -2y = -3y -3x = -3y Divide each side by '-3'. x = y Simplifying x = y
| 2(5)-5y=10 | | 2(4)-5y=10 | | 2(3)-5y=10 | | 2(2)-5y=10 | | 2(1)-5y=10 | | fc=0.6x^2-36x | | 8[3-(4+6x)]-4x=-10+2(1-26x) | | log(3x)=1.8 | | 6x-7=4-x | | 3(5)-6=9x | | 3(4)-6=9x | | 3(3)-6=9x | | 6r+6=24 | | 3(1)-6=9x | | -h=g-vh | | 3y-6=9(2) | | (-45+33)-7= | | -6=9x | | 11x^2+1-[5(x^2-7)+5]= | | 3x-(2-x)=4-2x | | f(x)=0.6x^2-36x | | p(x)=9x | | 6r+7r=13+7r | | 10x^2+8-[6(x^2-4)+9]= | | f=ax^2-bx | | 6-3(-7+10)=-3 | | -30=q-1q | | -10+11= | | 3d+4a=11d-2b | | (3x-2y+1)dx+(3x-2y-3)dy=0 | | 54=4(5+s) | | m+3=26 |